1983
DOI: 10.1016/s0022-5347(17)51405-6
|View full text |Cite
|
Sign up to set email alerts
|

Intractable Hematuria and Formalin

Abstract: Massive hematuria, which is most frequently caused by radiation for pelvic malignancies, after treatment with cyclophosphamide or secondary to aggressive anticoagulation, represents a vexing problem for the practicing urologist. The existence of numerous therapeutic approaches results from the lack of an effective therapeutic modality. Lately, formalin seems to offer a new hope for the treatment of intractable hematuria. Analysis of published results after treatment with formalin revealed generally excellent r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

1985
1985
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 19 publications
0
20
0
1
Order By: Relevance
“…9,11,12,[15][16][17] In their comprehensive review of the 235 previously reported cases of formalin use, Donahue and Frank (1989) identified a trend towards increasing complete response rates with 10% intravesical formalin (83% complete response), as compared to 5% formalin (78% complete response) or 1% formalin (71% complete response) solutions, although this was not statistically significant. 16 Here, we identified a success rate of 63% at a median followup of eight months with the initial use of 1% formalin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…9,11,12,[15][16][17] In their comprehensive review of the 235 previously reported cases of formalin use, Donahue and Frank (1989) identified a trend towards increasing complete response rates with 10% intravesical formalin (83% complete response), as compared to 5% formalin (78% complete response) or 1% formalin (71% complete response) solutions, although this was not statistically significant. 16 Here, we identified a success rate of 63% at a median followup of eight months with the initial use of 1% formalin.…”
Section: Discussionmentioning
confidence: 99%
“…12,16,18 From the limited available literature, it is clear that higher formalin concentrations are associated with an increased risk for adverse events. 12,16 Serious complication rates, as high as 50-75%, have been reported in patients undergoing 10% formalin instillation, albeit in small series. 11,15 For instance, in one series, 40% of patients required urinary diversion after intravesical formalin instillation for complications related to the procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It probably is the most effective method for controlling massive hematuria and the most dangerous. Formalin causes precipitation of cellular proteins of the bladder mucosa [12]. It also acts through its occluding and fixative action upon telangiectatic tissue and small capillaries [12].…”
Section: Discussionmentioning
confidence: 99%
“…A contact period of 3-30 minutes has been used in various studies by clamping the catheter. Serious complications which can be encountered during the procedure include a small contracted bladder, urinary incontinence, VUR, ureteric strictures, vesico-ureteric junction obstruction with hydro-ureteronephrosis, acute tubular necrosis with anuria, vesico-vaginal fistula, vesico-ileal fistula, a toxic effect on myocardium, and rupture of the bladder (Godec et al, 1983). Deaths have been reported in extreme cases.…”
Section: Formalinmentioning
confidence: 99%